ANALYSIS OF THE VOLUME OF GENERATION AND DEVELOPMENT OF WAYS TO USE WOOD RESIDUES AND WASTE FROM THE PRO-DUCTION ACTIVITIES OF A FURNITURE ENTERPRISE - Kyianka, Volodymyr; Gayda, Serhiy (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
The study addresses the generation, structure, and utilization of wood residues and composite waste in furniture manufacturing within the framework of circular economy principles. The research is based on empirical data from a furniture enterprise for the period 2022–2024 and focuses on identifying efficient pathways for waste valorization. A material flow analysis combined with a mass-balance model was applied to evaluate waste streams and their allocation to reuse routes, including mechanical recycling, panel production, and bioenergy. The results indicate a significant reduction in total waste generation from 54.80 m3 in 2022 to 30.48 m3 in 2024 (–44%), mainly due to improved processing efficiency and optimized cutting strategies. Solid offcuts decreased by 44%, while sawdust and shavings showed reductions of 47% and 45%, respectively. The proposed utilization model ensured approximately 95% landfill diversion, with 28.95 m3 redirected to secondary use streams. The economic assessment demonstrated a total annual effect of approximately UAH 0.25 million, primarily driven by mechanical reuse (≈89% of total margin). The energy recovery potential from fine fractions reached 11.35 MWh/year, with avoided CO2 emissions ranging from 2.29 to 3.86 tons depending on substitution scenarios. The novelty of the research lies in integrating cascade wood utilization with an enterprise-level material balance model that aligns technological, economic, and environmental parameters. The practical value consists in providing a replicable tool for resource efficiency management and sustainable production in furniture manufacturing.